Tensegrity space structures : static, kinematic and stability behaviour - Sulaiman, Muzzammil (Department of Civil Engineering, 2014)
This dissertation is an in depth study of the design and behaviour of tensegrity space structures. It deals with various aspects of these systems including form-finding and analysis. The dynamic relaxation method is employed to develop a software solution for the design and analysis of tensegrity systems with a focus on its application to irregular forms. This method employs an iterative finite difference approach to integrate nodal parameters over time increments.